2017
DOI: 10.1038/s41598-017-15207-w
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Phosphatidylinositol 3-kinease suppresses formation and progression of experimental abdominal aortic aneurysms

Abstract: Accumulating evidence suggests an important role of Phosphatidylinositol 3-kinease (PI3K) pathway in inflammatory cells infiltration. Given  the essential role of inflammatory cells infiltration during the formation and progression of abdominal aortic aneurysm (AAA), to investigate the possibility of preventing AAA formation and progression via targeting PI3K is anticipated. Here, experimental AAAs was created in rats by transient intraluminal porcine pancreatic elastase (PPE) infusion into the infrarenal aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…NF-кB is closely associated with the regulation of inflammation and immune responses in the physiological or pathophysiological processes of AAA [ 29 ]. Several stimuli, such as angiotensin II, ROS, and MMP-9, activate NF-κB signalling in AAA diseases [ 30–32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-кB is closely associated with the regulation of inflammation and immune responses in the physiological or pathophysiological processes of AAA [ 29 ]. Several stimuli, such as angiotensin II, ROS, and MMP-9, activate NF-κB signalling in AAA diseases [ 30–32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Akt signalling was reported to be increased during AAA development, and suppression of Akt inhibited AAA formation [ 29 ]. Our results showed that upon returning to normal nutrient medium, 3T3-L1 adipocyte-differentiated cells significantly suppressed the glucose- and serum deprivation-induced increase in phosphorylated-Akt expression.…”
Section: Discussionmentioning
confidence: 99%
“…ADAM9, modulated by miR-126, could induce inflammatory cascades and the infiltration of macrophages into the aortic wall [ 20 ]. Additionally, knockdown of ADAM9 suppressed aneurysm formation through PI3K/AKT/NF-κB pathway inhibition, an activated pathway in the murine aneurysm model [ 67 ]. Therefore, ADAM9 can induce retinal disorders as well as pathological vascular diseases.…”
Section: Pathological Roles Of Adam9 In Neurodegenerative and Retimentioning
confidence: 99%
“…Numerous animal models, such as angiotensin II (Ang-II)-induced AAA mouse model, were developed to explore more treatment methods for the disease [ 6 - 8 ]. Several lines of evidence have revealed that the number of smooth muscle cells (SMCs) in AAA tissues is significantly reduced, and the pathogenesis of AAA is closely associated with inflammation in the aortic wall and extracellular matrix degeneration [ 9 , 10 ]. Hence, it is necessary to investigate the pathological mechanism of AAA and find new molecular targets for AAA treatment.…”
Section: Introductionmentioning
confidence: 99%